Environment impact assessment : - Lawrence, David P (Wiley-interscience, 2003)
This book challenges the prevailing assumption that Environmental Impact Assessment (EIA) should be structured around a unitary EIA process. The book begins by identifying, through a scenario, eight recurrent problems in EIA practice. The characteristics of multiple variations of conventional EIA processes, at both the regulatory and applied levels, are then presented. The residual problems that remain after the conventional processes are described and assessed providing the springboard for a description and analysis of eight alternative EIA processes.